PENGARUH KEPUASAN KONSUMEN TERHADAP PEMBENTUKAN KOMITMEN PELANGGAN DAN e-WOM PADA PENGGUNA APLIKASI e-MONEY “OVO” - Naulia Oktaviani; Widji Astuti; Achmad Firdiansjah (Jurnal Manajemen dan Pemasaran Jasa, 2019)
The purpose of this study was to examine the effect of customer satisfaction on the formation of customer commitment and e-WOM. Commitments are divided into three, namely affective commitment, continuance commitment and normative commitment and are located as intervening variables. Data was collected from 100 e-money “OVO” application users in Malang who met the criteria determined by the researcher. The hypothesis is tested by path analysis using Smart PLS 3.2. The results of the study show that consumer satisfaction has a strong influence on the formation of affective commitment and normative commitment and encourages e-WOM behavior. Continuous commitment has no significant effect on e-WOM, because some customers decide to continue using OVO but choose not to disseminate OVO information to others. There is an indirect effect between customer satisfaction and EWOM through costumer commitment as intervening. Managerial advice that can be obtained is that the position of customer satisfaction is very important in marketing digital products because it is able to build customer commitment and encourage consumers to participate in disseminating product information to the public. The limitations of this study are in terms of numbers that are less representative so that further research is expected to expand the area used as the object of study and increase the number of respondents to the study so that the results obtained are expected to be better.